Cumulative versus Gravity-based Accessibility Measures: Which One to Use? - Manuel Santana Palacios; Ahmed El-geneidy (Findings)
This paper compares two popular approaches to calculate access to jobs by public transport: gravity and cumulative opportunities. Using data on commute patterns and public transport schedules from Montreal, Canada, we find cumulative opportunities-based measures estimated at the mean transit commute time and gravity-based measures generated through various decay functions are highly correlated -- all above 0.9. This finding holds even when replicating the analysis for low- and non-low-wage jobs available in the same metropolitan region. These findings strongly suggest that easy-to-communicate and -operationalize cumulative opportunities accessibility constructs measured at the mean commute time perform similarly to more theoretically-sound gravity-based measures.